Development of Sports and Health Physical Education Learning E-Module Pencak Silat Material Accompanied by Physical Fitness Exercise Activities for Class VII Students (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the development of sports and health physical education learning e-modules for pencak silat material accompanied by physical fitness training activities for seventh grade students. Research is a type of development research (Research & Development). This research was conducted in class VII SMP Pertiwi Siteba, SMP Angkasa Lanud and SMP IT Budi Mulya, Padang City. The instrument in this study is a questionnaire that has been validated by experts. The data analysis technique is a quantitative descriptive analysis technique. The results of the study concluded that the level of product feasibility was 93.05% and large-scale trials obtained data of 86.21% of students strongly agreed to use the resulting e-learning module. It can be concluded that based on the validation tests and trials conducted, the e martial arts learning module for class VII students is